Predictors of Internship Performance among Graduating Teacher Education of Nueva Ecija University of Science and Technology - Samonte, Kenneth; de Guzman, Pastora (JPAIR Institutional Research, 2018)
Internship in the world of teaching is not only the learning tools but also a good chance for students to understand the workplace culture within the school environment. It has been progressively growing regarding its integration into the academic curriculum of higher education institutions and as a prerequisite for graduation locally and internationally. This study aimed to identify the predictors which may contribute to internship performance among graduating teacher education. The researchers used the descriptive research method with the use of questionnaires as the main tools in gathering data. Weighted mean and standard deviation was used in the study. A total of 100 respondents were involved in this study using simple random sampling. Pearson Product Moment (PPM) was used to determine the relationship between the variables. Results showed that internship performance in terms of lesson planning, teaching method, classroom management, communication skills and teachers’ personality were assessed outstanding by the respondents. And internship performance in terms of teachers’ personality shows significant relationship on the organizational environment. From the findings, it was recommended by the researchers that internship coordinators should conduct regular visitations to ensure that punctuality and attendance are being witnessed and practiced. And it is also recommend that the College of Education should coordinate with the schools and other stakeholders to designate specific individual to manage and supervise the interns.